Organizational Culture and Organizational Climate as a Determinant of Motivation and Teacher Performance - Rivai, Rivai; Umar Gani, Mursalim; Murfat, Moh. Zulkifli (Advances in Social Sciences Research Journal, 2019)
The purpose of the study is to partially analyze the effects of: (1). organizational culture and organizational climate towards motivation and teachers performance of Public senior high school. (2) Motivation towards the teacher’s performance of Public senior high school. This research was conducted at Public senior high school in West Sulawesi Province. The study population was a teacher Public senior high school who had in been certified as many as 728 people. A sample of 201 respondents was taken proportionally. Data analyzed using Structural Equation Model (SEM). The results of the study show that: (1) Organizational culture has a positive significant effect on teacher motivation and performance (2) Organizational climate has a negative significant effect on teacher motivation and performance. (3) Motivation has a positive significant effect on teacher performance.